2019
DOI: 10.1016/j.celrep.2019.06.098
|View full text |Cite
|
Sign up to set email alerts
|

A Spontaneous Aggressive ERα+ Mammary Tumor Model Is Driven by Kras Activation

Abstract: SUMMARY The NRL-PRL murine model, defined by mammary-selective transgenic rat prolactin ligand rPrl expression, establishes spontaneous ER+ mammary tumors in nulliparous females, mimicking the association between elevated prolactin (PRL) and risk for development of ER+ breast cancer in postmenopausal women. Whole-genome and exome sequencing in a discovery cohort (n = 5) of end-stage tumors revealed canonical activating mutations and copy number amplifications of Kras. The frequent mutations in this pathway wer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 78 publications
(119 reference statements)
0
22
0
Order By: Relevance
“…In 2001, D'Cruz et al described sustained oncogenic transformation following spontaneous mutagenesis of Kras2 in an inducible c-Myc mammary tumorigenesis model [59]. In 2019, Campbell et al reported spontaneous alterations in Kras expression and activity in the aggressive ERα + NRL-PRL postmenopausal murine model, that drove neoplastic transformation [60]. Additionally, the Kras Q61H mutation was identified in primary tumors from a triple negative murine model by Liu et.…”
Section: Discussionmentioning
confidence: 99%
“…In 2001, D'Cruz et al described sustained oncogenic transformation following spontaneous mutagenesis of Kras2 in an inducible c-Myc mammary tumorigenesis model [59]. In 2019, Campbell et al reported spontaneous alterations in Kras expression and activity in the aggressive ERα + NRL-PRL postmenopausal murine model, that drove neoplastic transformation [60]. Additionally, the Kras Q61H mutation was identified in primary tumors from a triple negative murine model by Liu et.…”
Section: Discussionmentioning
confidence: 99%
“…1 ), suggest Ras may cooperate with hPRLrL+I heterodimers during transformation. Furthermore, recent studies with a transgenic PRL over-expression mouse model have implicated KRAS signaling involvement in PRL-dependent mammary neoplasias 6 , 26 . KRAS promotes metastatic dissemination, and therefore, is strongly correlated with worse overall patient outcome 27 .…”
Section: Resultsmentioning
confidence: 99%
“…KRAS holds a prominent cooperative role with hPRLr in breast cancer pathogenesis. For example, in characterizing a PRL-driven mammary cancer mouse line (NRL-PRL), genomic analyses uncovered consistent oncogenic KRAS somatic mutations/amplifications in all primary tumors, which was not found in pre-neoplastic glands 26 . These findings coincided with recent discoveries of significant KRAS involvement in breast cancer metastatic dissemination, mirroring the in vivo results presented herein 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequencing data from genetically engineered mouse models is largely lacking, with only a few models having been sequenced 30 , 36 38 . SNV mutation rates between previous studies and ours indicate similarities, and small discrepancies may be explained through differences in data processing methods.…”
Section: Discussionmentioning
confidence: 99%